Meningkatkan Kemampuan Kognitif dalam Mengetahui Sebab Akibat Melalui Kegiatan Membuat Minuman Berbagai Rasa - R F Ahmada (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
This research was conducted to improve cognitive abilities in knowing cause and effect through activities of making various flavors of drinks, this research was conducted at Dharma Wanita Kindergarten, Kedak Village, Cement District, Kediri Regency, the method used in this study was classroom action research, this study used cycle 1 and cycle 2 is in the process of improving students' cognitive abilities. And from the results of the data that has been obtained it shows that the increase in students' cognitive abilities has increased well starting from cycle 1 to cycle 2, these results will not work well if the aspects used are not associated with the game of cause and effect in the activity of making various flavored drinks.